AKTIVITAS ANTIBAKTERI NIRA LONTAR TERFERMENTESI DENGAN VARIASI LAMA WAKTU FERMENTASI TERHADAP BAKTERI GRAM POSITIF (Staphylococcus aureus) DAN GRAM NEGATIF (Escherichia coli) - Erda Eni Rame Hau; Eni Rohyati (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2018)
This study aims to determine the effect of spontaneous fermented nira with different treatment time to gram positive and gram negative bacteria. The research was conducted in November 2017 at the Animal Health Laboratory, Kupang State Agricultural of Polytechnic and Veterinary Public Health Laboratory, Faculty of Veterinary Medicine, Nusa Cendana University, Kupang, NTT. Samples of bacteria used in this study were Staphylococcus aureus and Escherichia coli bacteria. The fermented of nira lontar from 4 fermentation time (1 day (N1), 2 days (N2), 3 days (N3), and 4 days (N4)) were then collected to test the antimicrobial activity in inhibiting the growth of the microorganism. Fermentation was carried out for 4 days because previous research showed that the optimum growth of lactic acid bacteria in fermented palm was on the 4th day. This study used the Kirby-Bauer disc method, in which antibacterial activity was described by the diameter of the inhibition zone. The results showed that the mean diameter of the inhibitory zone of S. aureus with N1 material was 8.15 mm, while N2, N3, and N4 had the same diameter of 6.4 mm. There was a significant difference between the diameter of the N1 zone and the rest of the samples, as well as all treatments with Ciprofloxacin positive control antibiotics. Different trends were indicated by E. coli, where there were no significant differences between N1, N2, and N3 diameters with values of 9.2 mm, 8.95 mm, and 8.1 mm, respectively, but they were significantly different from the diameter N4 of 6.4mm, and all treatments were significantly different with Ciprofloxacin positive control antibiotics. It can be concluded that spontaneous fermented nira lontar at four different fermentation time intervals have antimicrobial activity against gram-positive and gram-negative bacteria, with statistically significantly different inhibitory activity among different fermentation days. Moreover, fermented nira lontar has higher inhibitory activity on gram-negative bacteria, E. coli compared to gram-positive bacteria, S. aureus.